THE CONCEPT OF WAQF FROM WORLDVIEW THEORY: The Study of Sharia-Philosophy - Khasib Amrullah; Mulyono Jamal; Eko Nur Cahyo; Usmanul Khakim; Khurun'in Zahro' (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
This article describes the structure of the waqf concept from a worldview theory perspective. Worldview is simply a fundamental belief system concerning God, reality, man and truth, ethics, etc.; which serves as a guide for human life. A person's worldview will determine his behavior and actions. The next question is what kind of belief concept makes someone willing to do waqf? This article is a literature review that employs qualitative data with a philosophical approach. The data analysis method employs content analysis of data sources from the library. The result shows that the worldview analysis on waqf is a concept that was emerging from the Islamic worldview whose emergence was supported by various other fundamental concepts such as God, Prophets, Revelation, and Sharia (religion). It proves that the structure of the waqf concept is not as simple as handing over the property to Allah for the benefit of others. The peculiarity of such waqf concept seems impossible to be affirmed by the secular Western worldview, which is unable to affirm the concept of revelation, the Prophet, and religion. It also proves that the philosophical foundation of a waqf concept built on an Islamic worldview is very consistent, solid, and even has a broad spectrum that spans the worldly and the hereafter visions simultaneously.